Design and Psychometrics of "Health System Development Scale" - Ahmad Arabkhani; Hossein Dargahi; Raheb Ghorbani; Israfil Rushdi (Tehran University of Medical Sciences, 2023)
Background: The development of the health system increases the health level of the society. The present study was carried out with the aim of development of "Health System Development Scale". Methods: The study was qualitative-quantitative. For qualitative part, a semi-structured interview with 11 experts was conducted in a targeted manner with maximum diversity and the results were analyzed by open, central and selective coding method. For quantitative part, first the validity of the questionnaire was carried out through interviews with 10 experts. Finally, the construct validity was conducted according to the opinion of 220 experts by exploratory factor analysis (with the Kaiser-Meyer-Elkin scale) and confirmatory factor analysis (in the form of divergent, convergent validity and fit indices) using SPSS and Lisrel software. Reliability was also measured by calculating Cronbach's alpha coefficient and composite reliability. Results: The scale was designed with 40 statements obtained from the findings of the qualitative study. In the quantitative part, the appearance and content validity ratio of the dimensions of the questionnaire was qualitatively confirmed (for all statements between 0.80 and 0.1). Construct validity was done by exploratory and confirmatory factor analysis and convergent validity was between 0.53 and 0.75 and divergent validity was between 0.54 and 1. The internal consistency of the tool was approved with Cronbach's alpha coefficient between 0.75 and 0.86 and composite reliability coefficient was between 0.72 and 0.80. Conclusion: The validity and reliability of the scale was confirmed. It is suggested to use it to measure the level of development in the health system by experts in this field.